Predicting the social-emotional competence of adolescents based on the reflective capacity of the mother, regarding mediating role of family emotional conditions - Hooshmandi , Melika; Bahrami , Azam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research is to predict the socio-emotional competence of adolescents based on the reflective capacity of the mother, taking into account the role of the mediator of the family’s emotional atmosphere. Methods: The current research is descriptive and correlational. The statistical population of the research is the students of the second secondary level of the 3rd education district of Qom, who were studying in the academic year 2021-22. Using Cochran’s formula, the sample size equal to 363 people was selected based on the multi-stage cluster sampling method. In order to collect data, Zhou et al.’s socio-emotional competence questionnaire (2012), Hillburn’s emotional atmosphere questionnaire (1964) and Fonagy et al.’s reflective capacity questionnaire (2016) were used. Data analysis and evaluation of the proposed model was done through structural equation modeling and using SPSS and Lisrel software. Results: The results showed that the mother’s reflective capacity predicts the social-emotional competence of adolescents (β=0.68, P<0.001). Also, based on the findings of this research, the reflective capacity of the mother through the mediating variable of the emotional atmosphere of the family also has a predictive role on the socio-emotional competence of adolescents (β=0.89, P<0.001). Conclusion: According to the results of the research, higher levels of reflective capacity of mothers expect higher competence of teenagers in the studied age range and vice versa. Examining the reflective capacity of mothers in the form of existing tools and measures and having a picture of it can be useful in holding courses based on their mentalization